2018
DOI: 10.1136/jclinpath-2018-205277
|View full text |Cite
|
Sign up to set email alerts
|

Results of the UK NEQAS for Molecular Genetics reference sample analysis

Abstract: AimsIn addition to providing external quality assessment (EQA) schemes, United Kingdom National External Quality Assessment service (UK NEQAS) for Molecular Genetics also supports the education of laboratories. As an enhancement to the Molecular Pathology EQA scheme, a human cell-line reference sample, manufactured by Thermo Fisher Scientific (AcroMetrix), was provided for analysis. This contained many variants, present at frequencies between 1% and 17.9%.MethodsOne hundred and one laboratories submitted resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In fact, the median value of AF was 3.30% on slide A, 2.00% on slide B, and 0.30% on slide C. In this setting, however, the second‐look analysis, which entailed a visual inspection of all the slides, revealed a significant difference in the mutation detection between the first and second looks at all the slides (slide A, P = .014; slide B, P = .006; and slide C, P < .001). The challenge of detecting simultaneous mutations occurring in the BRAF gene has recently been highlighted by a study performed on a manufactured human cell line reference sample . Indeed, in this study, only 2 of 53 participating laboratories correctly identified all 8 variants engineered in the BRAF gene .…”
Section: Discussionmentioning
confidence: 88%
“…In fact, the median value of AF was 3.30% on slide A, 2.00% on slide B, and 0.30% on slide C. In this setting, however, the second‐look analysis, which entailed a visual inspection of all the slides, revealed a significant difference in the mutation detection between the first and second looks at all the slides (slide A, P = .014; slide B, P = .006; and slide C, P < .001). The challenge of detecting simultaneous mutations occurring in the BRAF gene has recently been highlighted by a study performed on a manufactured human cell line reference sample . Indeed, in this study, only 2 of 53 participating laboratories correctly identified all 8 variants engineered in the BRAF gene .…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, many reports have also lost the information of methodological details, particularly assay performance characteristics (such as LOD [52/66, 78.8%] and minimal depth of sequencing coverage [58/66, 87.9%]), and critical quality control (QC) metrics (52/66, 78.8%). It is significant to state that the assay performance characteristics and QC metrics were critical to reliably interpret the results as negative or positive and thus have a direct impact on treatment decisions . However, several reports overinterpreted the absence of a relevant mutation, without providing such information.…”
Section: Resultsmentioning
confidence: 99%
“…Because circulating tumor DNA (ctDNA) can provide a comprehensive profiling of tumor aberrations, ctDNA analysis is emerging as a valuable tool for the guidance of targeted therapy , the observation of tumor dynamics , and the assessment of resistance to treatment . So far, many different approaches, including the amplification refractory mutation system (ARMS), digital polymerase chain reaction (dPCR), and next‐generation sequencing (NGS), have been applied for the detection of tumor aberrations in ctDNA . Because of the increased affordability, accessibility, high throughput, and unrestricted detection range, NGS‐based ctDNA analysis is now replacing ARMS, dPCR, and other ctDNA analysis approaches stepwise and is being extensively used in the clinical setting .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations